Non-Markovian renormalization of kinetic coefficients for drift wave turbulence - Zagorodny, A.; Weiland, J. (Condensed Matter Physics, 2001)
Statistical theory of non-Markovian effects in turbulent transport is applied to the description of plasma turbulence in a magnetoactive plasma in the drift-kinetic approximation. Renormalized transition probability is calculated with regard to non-Markovian effects and equations for the relevant kinetic coefficients are derived. It is shown that memory effects can be important for the description of transport under saturated turbulence. Статистична теорія немарковських ефектів у процесах турбулентного перенесення застосована до опису насичення плазмової турбулентності плазми в зовнішньому магнітному полі. Розраховано перенормовану ймовірність переходу з урахуванням немарковських ефектів і сформульовано рівняння для перенормованих кінетичних коефіцієнтів. Показано, що ефекти пам’яті можуть бути суттєвими при описі насичення турбулентності.